Steward of the Land : Selected Writings of Nineteenth-Century Horticulturist Thomas Affleck - Affleck, Thomas, 1812-1868 (Book collections on Project MUSE., 2014)
In the first collection of published writings of Thomas Affleck (1812-1868), Lake Douglas re-establishes the reputation of a tireless agricultural reformer, entrepreneur, and horticulturist. Affleck''s wide range of interests-animal husbandry, agriculture, scientific farming, ornamental horticulture, insects, and hydrology, among others-should afford him a celebrated status in several disciplines; yet until now his immense contributions remained largely unheralded. Steward of the Land remedies this oversight with a broad, annotated selection of Affleck''s works, rightfully placing him alongside.